2020
DOI: 10.1108/jpif-08-2019-0102
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a mortgage interest and capital deduction policy on house prices

Abstract: PurposeSince 2005, Belgian housing prices have strongly increased. As the timing coincides with the implementation of a new fiscal package in order to stimulate homeownership, our study attempts to provide an understanding whether the mortgage interest and capital deduction (MICPD) policy has had the side-effect of increasing housing prices while, at the same time, controlling for key housing price determinants.Design/methodology/approachA fixed-effects regression model is used on a panel dataset of the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Although it has been long established that interest rates are a fundamental house price determinant (Muth, 1988), Vangeel et al (2020) found that interest rates' influence has been less substantial than commonly thought. Dr€ oes and Francke (2018) showed that liquidity (turnover) is a major determinant of house price dynamics and that gross domestic product, interest rates, and momentum coefficient estimates are upward biased if liquidity is not considered when calculating house returns.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Although it has been long established that interest rates are a fundamental house price determinant (Muth, 1988), Vangeel et al (2020) found that interest rates' influence has been less substantial than commonly thought. Dr€ oes and Francke (2018) showed that liquidity (turnover) is a major determinant of house price dynamics and that gross domestic product, interest rates, and momentum coefficient estimates are upward biased if liquidity is not considered when calculating house returns.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Although it has been long established that interest rates are a fundamental house price determinant (Muth, 1988), Vangeel et al. (2020) found that interest rates' influence has been less substantial than commonly thought.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interest rates (i.e. credit interest rate, government bond interest rate, mortgage interest rate) are considered as a variable in the studies of Ayuso and Restoy (2007), Égert and Mihaljek (2007), Pashardes and Savva (2009), Lebe and Akbaş (2014), Hatipoğlu and Tanrıvermiş (2017), Öztürk et al (2018), Mohan et al (2019), Gözübüyük and Koy (2020), Pontiggia and Sivitanides (2020) and Vangeel et al (2020). Taking into account these studies, we include interest rate as a variable in this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rent also plays a major role in housing prices because there is a high correlation between rent, housing prices and return on investment. Ayuso and Restoy (2007), Öztürk et al (2018) and Vangeel et al (2020) consider rent in explaining housing prices. By benefitting from these studies, we include rent as a variable and a positive relationship is expected between housing prices and rent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the academic literature on fiscal stimuli has focused almost exclusively on a single country (see e.g. Mian and Sufi, 2012;Nollet and Pattyn, 2014;Xhignesse and Verbist, 2019;Vangeel et al, 2020). Nevertheless, within (and outside) the European Union, various MID systems are implemented.…”
Section: Introductionmentioning
confidence: 99%